Season of birth distribution of elite tennis players - Edgar, S.; O'Donoghue, P. (Journal of Sports Sciences, 2005)
In many competitive sports, the use of a cut-off date for junior competition has been associated with a skewed birth date distribution in junior and senior players. The International Tennis Federation uses a junior competition year that commences on 1 January. The purpose of the current investigation was to describe the birth date distribution of 448 elite senior tennis players and 476 elite junior tennis players. There was a significant season of birth bias among elite senior players (P < 0.001), with 58.9% being born in the first 6 months of the year. There was also a significant season of birth bias among elite junior players (P< 0.001), with 59.5% being born in the first 6 months of the year. This pattern was observed in both male and female players as well as in players from different regions. The results provide evidence that it is the cut-off date for the junior competition year that is responsible for the skewed birth date distribution in tennis rather than regional or climatic factors.